Factor associated with mental health of patients during the COVID-19 pandemic - Rodea Montellano, Sarahi Elizabeth; Zárate Ayón, Erick José; Aguirre Garcia, Maria del Carmen; Olvera Pérez, Yolanda (International Journal of Research in Medical Sciences, 2023)
Background: The objective of this study was to determine the factors associated with the psychological impact on patients due to the COVID-19 pandemic in primary care. Methods: Study was analytical cross-sectional, prior authorization from the local research committee and informed consent, a survey was applied to 468 beneficiaries of the family medicine unit number 2 of Mexico City, which contained sociodemographic aspects, background, habits and behaviors, styles of coping, fear of death, and the DASS-21 scale. Descriptive and analytical statistics were used Chi square OR CI at 95% considering significance when p<0.05. Results: The sociodemographic profile of the studied population were 61.3% women, 40.6% in the range of 35-59 years, 44.4% undergraduate education, 42.1% single marital status and 23.5% professionals. 56% reported symptoms in any of the mental health subscales, of which 35% were depressive symptoms, 44.9% anxiety symptoms and 37.8% stress symptoms. Associated factors were fear of the pandemic, having suffered from COVID-19, being a professional, feeling of loneliness, changes in character. p 0.00. Conclusions: The pandemic affected mental health, so it is important to carry out an intentional search for the degree of repercussions to provide timely treatment as part of comprehensive care at the first level of care.